Pemanfaatan Media Sosial Dalam Pengembangan Usaha Kuliner Midal Tanta One Di Paslaten Satu Kecamatan Tomohon Timur - Rumimper, Zefanya Arnold Tarkinio; Rori, Yolanda P. I.; Tambas, Jane Sulinda (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to describe the utilization of social media on Midal Tanta One's culinary business in Paslaten One Village, East Tomohon District. This research was conducted from July to September. The data collection method is to use interviews and documentation methods. The data collected in this study are primary data obtained from direct interviews with respondents through questionnaires or questionnaires and secondary data in the form of other information related to this research through literature studies. provides various options for people to enjoy information, with the utilization of social media in the development of midal tanta one culinary business can increase consumers in culinary businesses. The presence of technology certainly brings good changes in the efficiency of the culinary business, because the use of this technology makes it easier for people to sell and buy food and drinks more easily and faster.